Responses of the Differentiated Intestinal Epithelial Cell Line Caco-2 to Infection With the Giardia intestinalis GS Isolate - Ma'ayeh, Showgy Y.; Knörr, Livia; Sköld, Karin; Garnham, Alexandra; Ansell, Brendan R. E.; Jex, Aaron R.; Svärd, Staffan G. (Frontiers in Cellular and Infection Microbiology, 2018)
Giardia intestinalis is a parasitic protist that causes diarrhea in humans, affecting mainly children of the developing world, elderly and immunocompromised individuals. Humans are infected by two major Giardia assemblages (i.e. genetic subtypes), A and B, with the latter being the most common. So far, there is little information on molecular or cellular changes during infections with assemblage B. Here, we used RNA sequencing to study transcriptional changes in Caco-2 intestinal epithelial cells (IECs) co-incubated with assemblage B (GS isolate) trophozoites for 1.5, 3 and 4.5 hours. We aimed to identify early molecular events associated with the establishment of infection and followed cellular protein changes up to 10h. IEC transcriptomes showed a dominance of immediate early response genes which was sustained across all time points. Transcription of inflammatory cytokines (e.g. cxcl1-3, ccl2, 1l1a and il1b) peaked at 1.5h and 3h of infection. Compared to co-incubation with assemblage A Giardia, we identified the induction of novel cytokines (cxcl8, cxcl10, csf1, cx3cl1, il12a, il11) and showed that inflammatory signaling is mediated by Erk1/2 phosphorylation (mitogen activated protein kinase, MAPK), nuclear factor kappa B (NFκB) and adaptor protein-1 (AP-1). We also showed that GS trophozoites attenuate P38 (MAPK) phosphorylation in IECs. Low amounts of IL-8, CXCL1 and CCL20 proteins were measured in the interaction medium, which was attributed to cytokine degradation by trophozoite secreted proteases. Based on the transcriptome, the decay of cytokines mRNA mediated by zinc finger protein 36 might be another mechanism controlling cytokine levels at later time points. IEC transcriptomes suggested homeostatic responses to counter oxidative stress, glucose starvation, and disturbances in amino acid and lipid metabolism. A large group of differentially transcribed genes were associated with cell cycle arrest and induction of apoptosis, which was validated at protein level. IEC transcriptomes also suggested changes in tight junction’s integrity, microvilli structure and the extracellular mucin layer. This is the first study to illuminate transcriptional and protein regulatory events underlying IECs responses and pathogenesis during Giardia assemblage B infection. It highlights differences compared to assemblage A infections which might account for the differences observed in human infections with the two assemblages.